2020
DOI: 10.1186/s40851-020-00158-4
|View full text |Cite|
|
Sign up to set email alerts
|

Natural selection, selective breeding, and the evolution of resistance of honeybees (Apis mellifera) against Varroa

Abstract: We examine evidence for natural selection resulting in Apis mellifera becoming tolerant or resistant to Varroa mites in different bee populations. We discuss traits implicated in Varroa resistance and how they can be measured. We show that some of the measurements used are ambiguous, as they measure a combination of traits. In addition to behavioural traits, such as removal of infested pupae, grooming to remove mites from bees or larval odours, small colony size, frequent swarming, and smaller brood cell size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 171 publications
0
28
0
Order By: Relevance
“…Grooming behavior in response to Varroa mites is also associated with injured mites falling from bees in colonies (Arechavaleta-Velasco & Guzman-Novoa, 2001) and the rate of damaged mites per hive varies according to the honey bee race. Van Alphen & Fernhout (2020) reported Italian race had an average of about 6% mite damage. In contrast, Rosenkranz et al (1997) recorded an average of 45% mite damage in Italian and Carniolan bees, while Africanized A. mellifera damaged 39%.…”
Section: Discussionmentioning
confidence: 98%
“…Grooming behavior in response to Varroa mites is also associated with injured mites falling from bees in colonies (Arechavaleta-Velasco & Guzman-Novoa, 2001) and the rate of damaged mites per hive varies according to the honey bee race. Van Alphen & Fernhout (2020) reported Italian race had an average of about 6% mite damage. In contrast, Rosenkranz et al (1997) recorded an average of 45% mite damage in Italian and Carniolan bees, while Africanized A. mellifera damaged 39%.…”
Section: Discussionmentioning
confidence: 98%
“…It is a different story with A. mellifera so far where the co-evolution is shorter than A. cerana . Nevertheless, several traits such as varroa sensitive hygiene (VSH) or suppressed mite reproduction (SMR) emerged and are still broadly studied [ 167 , 168 , 169 ]. In the meantime, chemical solutions were used to face this invader.…”
Section: Varroa Destructor Chemical and Semi-chemical Control Methodsmentioning
confidence: 99%
“… Berry et al (2022) demonstrated how regular and repeated treatment with oxalic acid vapour while significant capped brood area is present in the colony may work as a prophylactic approach, preventing varroa population growth, however is not capable of reducing varroa populations once they pass some treatment threshold as would be used in a IPM framework. Of note however is the significant IPM-conforming investment and emphasis on breeding bees which are mite-resistant; this is a topic which has been recently reviewed in detail by numerous authors ( Guichard et al, 2020 ; Le Conte et al, 2020 ; Mondet et al, 2020 ; Noël et al, 2020 ; Spivak and Danka, 2020 ; van Alphen and Fernhout, 2020 ). Alt-text: Box 1
Tracking Failures Negative results are underreported broadly in science; in applied sciences, this presents as a problem when ineffective treatments are not sufficiently and widely reported as inadequate.
…”
Section: Current Failures In Treatmentsmentioning
confidence: 99%